2009
DOI: 10.1186/bcr2450
|View full text |Cite
|
Sign up to set email alerts
|

Ku proteins interact with activator protein-2 transcription factors and contribute to ERBB2overexpression in breast cancer cell lines

Abstract: IntroductionActivator protein-2 (AP-2) α and AP-2γ transcription factors contribute to ERBB2 gene overexpression in breast cancer. In order to understand the mechanism by which the ERBB2 gene is overexpressed we searched for novel AP-2 interacting factors that contribute to its activity.MethodsKu proteins were identified as AP-2α interacting proteins by glutathione serine transferase (GST)-pull down followed by mass spectrometry. Transfection of the cells with siRNA, expression vectors and reporter vectors as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…It is possible that increased levels of DSBs resulting from reduced Ku levels may increase expression of ALT NHEJ factors via DNA damage response signaling pathways (37). Alternatively, Ku may transcriptionally regulate genes encoding ALT NHEJ proteins (3840). …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased levels of DSBs resulting from reduced Ku levels may increase expression of ALT NHEJ factors via DNA damage response signaling pathways (37). Alternatively, Ku may transcriptionally regulate genes encoding ALT NHEJ proteins (3840). …”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that PAR-3 occasionally localizes to the nucleus, as well as to cell-cell contacts (Fang et al, 2007). Biochemical studies indicated that PAR-3 can form a complex with the Ku80, Ku70 and catalytic subunits of DNA-dependent protein kinase (DNA-PK), which are also AP-2-binding proteins (Fang et al, 2007;Nolens et al, 2009;Traweger et al, 2008). Thus, PAR-3 might activate Girdin transcription by binding to the DNA-PK-AP-2 complex, and aPKC might be involved in processes such as protein assembly.…”
Section: Regulation Of Girdin Transcription By the Par-3 Cell Polaritmentioning
confidence: 99%
“…22 On the other hand, there are several reports indicating that Ku acts as a transcription factor: for example, in the repression of the human a-myosin heavy-chain promoter during heart failure; 23 or in contributing the oncogene ERBB2 overexpression in breast cancer cells by interacting with activator protein-2 transcription factors. 24 In this report we analyse the transcriptional regulation of murine Apaf1 and we demonstrate a functional interaction between Ku70/86 heterodimer and a specific region of Apaf1 promoter. We find that Ku acts as transcription repressor, leading to a downregulation of Apaf1 expression.…”
mentioning
confidence: 99%